Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical Utility of Amyloid PET Imaging in the Differential Diagnosis of Atypical Dementias and Its Impact on Caregivers. - Bensaïdane, Mohamed Reda; Beauregard, Jean-Mathieu; Poulin, Stéphane; Buteau, François-Alexandre; Guimond, Jean; Bergeron, David; Verret, Louis; Fortin, Marie-Pierre; Houde, Michèle; Bouchard, Rémi W; Soucy, Jean-Paul; Laforce, Robert (J Alzheimers Dis, 2016)
Recent studies have supported a role for amyloid positron emission tomography (PET) imaging in distinguishing Alzheimer's disease (AD) pathology from other pathological protein accumulations leading to dementia. We investigated the clinical utility of amyloid PET in the differential diagnosis of atypical dementia cases and its impact on caregivers. Using the amyloid tracer 18F-NAV4694, we prospectively scanned 28 patients (mean age 59.3 y, s.d. 5.8; mean MMSE 21.4, s.d. 6.0) with an atypical dementia syndrome. Following a comprehensive diagnostic workup (i.e., history taking, neurological examination, blood tests, neuropsychological evaluation, MRI, and FDG-PET), no certain diagnosis could be arrived at. Amyloid PET was then conducted and classified as positive or negative. Attending physicians were asked to evaluate whether this result led to a change in diagnosis or altered management. They also reported their degree of confidence in the diagnosis. Caregivers were met after disclosure of amyloid PET results and completed a questionnaire/interview to assess the impact of the scan. Our cohort was evenly divided between positive (14/28) and negative (14/28) 18F-NAV4694 cases. Amyloid PET resulted in a diagnostic change in 9/28 cases (32.1%: 17.8% changed from AD to non-AD, 14.3% from non-AD to AD). There was a 44% increase in diagnostic confidence. Altered management occurred in 71.4% (20/28) of cases. Knowledge of amyloid status improved caregivers' outcomes in all domains (anxiety, depression, disease perception, future anticipation, and quality of life). This study suggests a useful additive role for amyloid PET in atypical cases with an unclear diagnosis beyond the extensive workup of a tertiary memory clinic. Amyloid PET increased diagnostic confidence and led to clinically significant alterations in management. The information gained from that test was well received by caregivers and encouraged spending quality time with their loved ones.